Undiagnosed diabetes mellitus and tuberculosis infection: A population‐based, observational study from eastern China. Issue 3 (20th January 2020) - Liu, Qiao; Lu, Peng; Martinez, Leonardo; Peng, Hong; Zhu, Tao; Zhu, Limei; Wang, Jianming; Lu, Wei
Abstract: Background: China has the largest dual diabetes and tuberculosis epidemic globally. No studies from mainland China have assessed the relationship between tuberculosis infection and diabetes. We conducted a population‐based, observational study in eastern China to further explore this relationship. Methods: A blood glucose, Quantiferon, and tuberculin skin test were administered at baseline. We compared tuberculosis infection in nondiabetics and diabetics. The cohort was additionally screened for tuberculosis progression over 5 years. Results: Among 5405 participants, diabetics had elevated levels of Quantiferon and tuberculin positivity, largely driven by undiagnosed diabetics (compared with nondiabetics, adjusted odds ratios of 1.53; 95% confidence interval [CI], 1.05‐2.23 and 1.58; 95% CI, 1.07‐2.35 for tuberculin and Quantiferon positivity). During follow‐up, the annual tuberculosis incidence was three times higher for diabetics compared with the entire cohort. Conclusions: These results suggest improving diabetic control through rapidly identifying undiagnosed diabetes may have indirect benefits to tuberculosis control. Targeting of preventive therapy to newly diagnosed diabetics at high‐risk for progressive tuberculosis in China should be considered.